Effect of change in coding rules on recording diabetes in hospital administrative datasets. (October 2016) - Assareh, Hassan; Achat, Helen M.; Guevarra, Veth M.; Stubbs, Joanne M.
Highlights: We measure the effect of causality mandate rule in coding diabetes as morbidity in hospital administrative datasets. Non-recorded diabetes rate increased by fourfold when the rule was in effect. Inter-hospital variation in recording diabetes increased by twofold. Appropriate adoption of protocols for clinical coding changes is essential to support the integrity of hospital administrative datasets. Abstract: Aim: During 2008–2011 Australian Coding Standards mandated a causal relationship between diabetes and inpatient care as a criterion for recording diabetes as a comorbidity in hospital administrative datasets. We aim to measure the effect of the causality mandate on recorded diabetes and associated inter-hospital variations. Method: For patients with diabetes, all admissions between 2004 and 2013 to all New South Wales acute public hospitals were investigated. Poisson mixed models were employed to derive adjusted rates and variations. Results: The non-recorded diabetes incidence rate was 20.7%. The causality mandate increased the incidence rate four fold during the change period, 2008–2011, compared to the pre- or post-change periods (32.5% vs 8.4% and 6.9%). The inter-hospital variation was also higher, with twice the difference in the non-recorded rate between hospitals with the highest and lowest rates (50% vs 24% and 27% risk gap). The variation decreased during the change period (29%), while the rate continued to rise (53%). Admission characteristics accounted for over 44% of the variation compared with at most two per cent attributable to patient or hospital characteristics. Contributing characteristics explained less of the variation within the change period compared to pre- or post-change (46% vs 58% and 53%). Hospital relative performance was not constant over time. Conclusion: The causality mandate substantially increased the non-recorded diabetes rate and associated inter-hospital variation. Longitudinal accumulation of clinical information at the patient level, and the development of appropriate adoption protocols to achieve comprehensive and timely implementation of coding changes are essential to supporting the integrity of hospital administrative datasets.